Possibility of forest grazing system in Hungary - Halász, András; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
The aim of this study was to report about current status of agroforestry in Hungary. Regular droughts endanger pasture based farming therefore all adaptive methodes are welcome. The latest modification of Forestry Act opened forest grazing, gives extra weeks on pastures. During autumn the critical daily weight gain can be achieved on fallen fruits and nuts only. Crowd sourced farming is getting popular around larger towns and cities. Agroforestry is a good add in marketing procedures, popularity keep growing. Complex livestock farming is sustainable in a close proximity of urban environment. Small number of animals with high added value combined with solvent demand are the corner stones in this kind of model.
Keywords: forestry; grassland management; black locust; dry habitat; heat stress